OPTIMIZING THE LEVEL OF KNOWLEDGE THROUGH DIGITAL LITERACY FOR COMMUNITIES SUFFERING FROM NON-COMMUNICABLE DISEASES - Rifahatul Mahmudah; Setiadi Syarli; Deni Maisa Putra; Tomi Jepisa (Jurnal Pengabdian Ilmu Kesehatan (JPIK), 2026)
Non-communicable diseases (NCDs) are the leading cause of death worldwide. The WHO reports that approximately 74% of global deaths are caused by NCDs, and in Indonesia, the figure reaches 76%. The increasing prevalence of NCDs, such as hypertension and diabetes mellitus, is also influenced by low health literacy and the public's ability to utilize digital information. This community service activity aims to optimize the knowledge level of NCD sufferers through a digital literacy approach in Korong Gadang Village, within the Kuranji Community Health Center (Puskesmas) working area. The implementation method includes education, demonstrations, and evaluation with post-implementation measurements based on digital media (PowerPoint and educational videos). The activity was conducted on December 23, 2025, involving 50 NCD sufferers. Results showed that the majority of respondents had a good level of knowledge after the intervention (68%), while 26% were in the adequate category and 6% were in the poor category. This community service activity demonstrates that digital literacy-based education is effective in increasing public understanding of NCD management. Thus, digital literacy can be a sustainable promotive and preventive strategy to support NCD control and improve the community's quality of life.